Evaluation of breast cancer prevention and quality of life by women after single breast mastectomy, grouped in the ‘Amazons’ post-mastectomy women’s club - Ridan, Tomasz; Ślęczkowska, Jadwiga; Sobota, Marzena; Ochałek, Katarzyna (Polish Journal of Public Health, 2011)
Introduction. Breast cancer is the most common cancer in women in Poland. As a result of surgical treatment both the physical and psychological condition of the patient deteriorate and so does the quality of life. Aim. The aim of the study was to evaluate the preventive measures for breast cancer in Poland and the effect of mastectomy on the quality of life, as viewed by women after single breast mastectomy of the “Amazons” Post-Mastectomy Women’s Club. Materials and methods. The research was carried out in a group of 78 women who had undergone single breast mastectomy with the average value of Age 56.88 (±8.49). The research results were subject to statistical analysis. The research made use of tests for Spearman’s and Pearson’s correlation coefficient  ρ, as well as of the Mann-Whitney U test, Levene’s, Student’s and Kolmogorov-Smirnov’s tests (p>0,05). Results. The study showed that out of individuals who reported to have been professionally active before the surgery, more than 70% have returned to work. For the majority of respondents, mastectomy did not have any effect on their relationships with family and friends. A statistical analysis pointed to a lack of relationship between evaluation of sex life variable and age, between the education level of respondents and the frequency of performing self check-ups and the level of education and frequency of undergoing medical check-ups. No correspondence was found between age of the respondents and frequency of performing self check-ups. The standard of cancer prevention in Poland was rated as average or good. The Mann-Whitney U test showed no relationship between rating of cancer prevention in Poland and place of residence. Conlusions. As a result of mastectomy, the general physical fitness of the patient deteriorates, which is reflected in both the person’s professional and private life. Mastectomy influences the patient’s perception of her body; however, when the patient is in a long-term and stable relationship with her partner, her condition has no considerable effect on their sex life. Level of education and age of the patient do not have any effect on the regularity of medical check-ups and self check-ups.